Economic growth and development in Singapore past and future - Peebles, Gavin, 1947-; Wilson, Peter, 1951-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2002)
In this book Gavin Peebles and Peter Wilson offer an historical overview of the rapid growth and development of the Singapore economy, detailing the institutions and policies which have made this growth possible. They examine the current state of the economy and its future in terms of prospective growth and structural change.
1. Introduction, themes and structure of the book -- 2. Foundations for growth -- 3. The growth experience -- 4. Structural change -- 5. Monetary, financial and fiscal aspects -- 6. Development indicators and welfare -- 7. Trade, trade policy and growth -- 8. International finance and growth -- 9. Back to the future : continuity or real paradigm shift?
Includes bibliographical references (p. 287-319) and index.
Keywords: Singapore -- Economic conditions; Singapore -- Economic policy; Electronic books